'If you have good skin, you are god. If you have bad skin, you are a piece of rubbish'. Mastery of shame and anger in treatment-resistant body dysmorphic disorder: a single case study. (29th July 2016) - Sündermann, Oliver; Wheatley, Jonathan; Veale, David
Abstract: Body dysmorphic disorder (BDD) is characterized by a preoccupation with a perceived flaw in one's appearance, and is often emotionally linked with early adverse experiences. Cognitive behavioural therapy (CBT) is effective but may not resolve shame and anger that can be at the emotional root of BDD. This paper presents a single-case study of a 25-year-old man with a history of treatment-resistant BDD characterized by a preoccupation with facial skin linked to a developmental history of sexual abuse and bullying. He was treated at a national residential specialist unit for 16 weeks during which time he received three individual 1-hour weekly CBT sessions (42 sessions overall), and participated in the residential group programme and therapeutic community. CBT was enhanced using imagery rescripting, compassion-focused therapy and family work to specifically target shame and anger-based past experiences. Severity of BDD was assessed with the BDD-Yale–Brown Obsessive Compulsive Scale (BDD-YBOCS) at pre-, mid-, post-, 3-month and 18-month follow-ups; a weekly self-report measure (Appearance Anxiety Inventory), and a client-drawn self-portrait of his perceived skin flaws at pre- and post-treatment. Treatment outcome was positive. The BDD-YBOCS dropped 94% from the extremely severe range pre-treatment to the sub-clinical range post-treatment. BDD symptoms improved progressively throughout treatment, and when the emotions of anger and shame were resolved (as reported by the client) fell to the non-clinical range. Gains were maintained at 18-month follow-up. We conclude that enhancing CBT for BDD using emotion-focused techniques is to be recommended, particularly when emotional memories continue to affect body shame.